2022
DOI: 10.1097/sla.0000000000005720
|View full text |Cite
|
Sign up to set email alerts
|

Domains of Frailty Predict Loss of Independence in Older Adults After Noncardiac Surgery

Abstract: Importance: Preoperative frailty has been consistently associated with death, severe complications, and loss of independence (LOI) after surgery. LOI is an important patient-centered outcome, but it is unclear which domains of frailty are most strongly associated with LOI. Such information would be important to target individual geriatric domains for optimization. Objective: To assess whether impairment in individual domains of the Edmonton Frail Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…In the SAGES I cohort, we found that preoperative frailty measures using both the FI and FP were associated with the development of postoperative delirium. The FI identified slightly more than one‐third of the patients as frail, and the FP identified slightly fewer than one‐third of patients as frail, consistent with other cohorts of older adults undergoing surgery 34,35 . Frail patients had approximately twice the relative risk of developing postoperative delirium.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the SAGES I cohort, we found that preoperative frailty measures using both the FI and FP were associated with the development of postoperative delirium. The FI identified slightly more than one‐third of the patients as frail, and the FP identified slightly fewer than one‐third of patients as frail, consistent with other cohorts of older adults undergoing surgery 34,35 . Frail patients had approximately twice the relative risk of developing postoperative delirium.…”
Section: Discussionsupporting
confidence: 78%
“…The FI identified slightly more than one-third of the patients as frail, and the FP identified slightly fewer than one-third of patients as frail, consistent with other cohorts of older adults undergoing surgery. 34,35 Frail patients had approximately twice the relative risk of developing postoperative delirium. We found the FI was more strongly associated with delirium incidence than the FP after considering comorbidity and preoperative cognition.…”
Section: Discussionmentioning
confidence: 99%